The role of the p53 and nucleotide excision repair proteins in the base excision repair of methylene blue plus visible light induced DNA damage - Kassan, Shaqil (My University, 2005)
The nucleotide excision repair pathway (NER) has been shown to efficiently remove bulky base lesions from the DNA, including those induced by solar light. It has been suggested that the NER pathway may be involved also in removing smaller oxidative base lesions from the DNA. Oxidative damage in the cell is caused by cellular aerobic respiration, with base damage to the nucleotides of the DNA being the most biologically relevant. One of the most common oxidative base lesions in the genome is the 7 ,8-dihydro-8-oxoguanine (8-oxoG). This lesion is pre-mutagenic since it can base pair with equal efficiency to the correct cytosine base, or the incorrect adenine base during DNA replication. Oxidative damage, including 8-oxoG, is repaired primarily by the base excision repair (BER) pathway, which is a multi-step, multi-protein pathway similar to NER. One key protein involved in both BER and NER is the p53 protein, which can act as a transcription factor and protein regulator to influence DNA repair. We have used a recombinant non-replicating human adenovirus, Ad5HCMVlacZ, which expresses the ~-galactosidase (~-gal) reporter gene, to examine the role of several NER proteins and the p53 protein in the BER of oxidative damage in human cells. Methylene blue (MB) acts as a photosenstizer, and after irradiation by visible light (VL) produces reactive oxygen species that cause 8-0xoG in the DNA. By infecting several normal, NER deficient and p53 deficient -tumor, primary and transformed fibroblast cell lines with a MB+VL-treated Ad5HCMVlacZ reporter construct, we were able to determine the host cell reactivation (HCR) of the oxidatively damaged reporter. Results indicate that the HCR of the MB+VL-treated reporter and the expression of p53 are enhanced by UVC pretreatment in normal human fibroblasts, suggesting that p53 may be involved in inducible BER. In addition, increased expression of p53 facilitated by pre-infection of normal cells with p53 expressing Ad5p53wt similarly enhanced HCR in the normal fibroblasts, giving further evidence that increased expression of p53 alone enhances BER. In contrast, although UVC pretreatment of p53 compromised cells resulted in enhanced HCR, the enhanced HCR did not correlate with enhanced p53 expression, suggesting that enhancement in BER can result from both p53 dependent and p53 independent mechanisms. We report also that HCR of the MB+VL-treated reporter gene was substantially reduced in SV40-transformed XP-C cells, with little or no reduction in SV40-transformed XPA, XPD, XPF, XPG and CSB cells, suggesting a role for the XPC protein in the BER ofMB+VL-induced DNA damage. In particular, the XPC protein appears to be involved in both the constitutive and inducible aspects of BER, as the HCR of the MB + VL-treated reporter was reduced in 3 UVC pretreated as well as untreated XP-C primary human fibroblast strains. In addition, pre-infection of cells with Ad5p53wt, resulted in an enhanced HCR of normal but not XP-C deficient fibroblasts consistent with a p53 dependent involvement of the XPC protein in BER of MB+VL-treated DNA. Additional studies were also conducted to determine the cell sensitivity of normal and NER deficient SV40-transformed cell lines to MB and MB+VL. The results show that MB alone and MC+VL are toxic to cells, and that cells deficient in NER are not more sensitive to MC or MB+VL compared to NER proficient normal cells. In fact, the NER deficient cell lines were more resistant to MB alone compared to NER proficient normal cells. In particular, although the SV40- transformed XP-C cell line showed a significant reduction in HCR of the MB-Vl-treated reporter gene, suggesting a deficiency in the repair of MB+VL-induced DNA damage, the SV40-transformed XP-C cells were not more sensitive to MB or MB+VL. This suggests that the toxicity of human cells to MB and MB+VL results primarily from damage to cellular components other than DNA such as membrane structures including the mitochondria and lysozomes as has been reported for other photosensitizers.
Keywords: nucleotide excision repair proteins, methylene blue, oxidative damage